HUBUNGAN MINAT MEMBACA DENGAN KEMAMPUAN MENULIS TEKS PIDATO SISWA KELAS X SMA NEGERI 7 KOTA LUBUKLINGGAU - Nilawati, Nilawati (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
The purpose of the study to explain the interest in reading, the ability to write a text to speech. In this study was text reading and writing text to speech ability tests, the reseach method used is descriptive correlational method that consist of two variables. The population of this study were all students of class X SMA Negeri 7 Kota Lubuklinggau academic year 2015/2016. This sample is the total sample as the sample is less than 100. Tecnik date collection used in this study is a questionnaire tests for reading and wrting text to speech ability test in reseach interest in reading the average student belonging to the category of very happy to read (3,76) and the ability to write text to speech average belong to the category good (76,77) based on the result of test analysis obtained correlation r = 0,4293 count greater than r table = 0,364 Ha than H0 resected and accepted. So that it can be concluded that the relationship small (low) between interest in reading with the ability two write text to speech or students in the classroom X SMA Negeri 7 Kota Lubuklinggau.